Application Of Performance Management On D'sayur Tanjungpinang - Alya Tri Rahmayani; Cindy Emilia; Delfia Oktalina; Septi Listiana; Satriadi Satriadi (Pusat Riset dan Inovasi Nasional, 2024)
D’Sayur as an e-commerce platform that focuses mainly on selling fresh vegetables, faces rapid market dynamics and fierce competition. Operational complexity and optimal customer service needs lead to the need to implement performance management. The purpose of this study is to examine the impact of the implementation of performance management on Dsayur with a focus on operational changes, customer feedback and its contribution to D’Sayur's business growth located Jl. R.H.Fisabilillah No.7 KM 8 Atas, Tanjungpinang. Research methods include implementation management analysis, operational monitoring and customer response evaluation. A qualitative approach is used to refine the results. The implementation of Sayur activities is able to improve operational efficiency, achieve better customer satisfaction and have a positive impact on the overall growth of the company. The results of this study provide an in-depth understanding of the importance of performance management to support the smooth operation and growth of the vegetable business. The impact includes the development of performance management strategies that are targeted and responsive.